Biometric Predictability in Combined Cataract Surgery and Ahmed Glaucoma Valve Implantation Depending on Tube Position - Marta A (Dove Medical Press, 2021)
Ana Marta,1,2 João Coelho,1 Rita Vieira,1 Ana Figueiredo,1 Rita Reis,1 Isabel Sampaio,1 Maria João Menéres,1,2 Pedro Menéres1,2 1Department of Ophthalmology, Centro Hospitalar e Universitário do Porto, Oporto, Portugal; 2Instituto de Ciências Biomédicas Abel Salazar, Oporto, PortugalCorrespondence: Ana MartaDepartment of Ophthalmology, Centro Hospitalar e Universitário do Porto, Largo do Prof. Abel Salazar, Porto, 4099-001, PortugalEmail analuisamarta2@gmail.comPurpose: To compare the predictability of biometric results in patients undergoing cataract surgery combined with Ahmed glaucoma valve (AGV) implantation according to tube position.Methods: A retrospective cohort study was performed in patients who underwent phacoemulsification surgery combined with AGV implantation with the tube in posterior (group PC) and anterior (group AC) chamber, between November 2012 and April 2020. The main outcome was the mean biometric prediction error, according to tube position, using different formulas.Results: The study included 49 eyes of 36 patients, 23 eyes in group PC and 26 eyes in group AC. Gender (p=0.774), age (p=0.822), type of glaucoma (p=0.168), preoperative correct distance visual acuity (p=0.139), axial length (p=0.765), anterior chamber depth (p=0.351), keratometry (p=0.577) and intraocular lens power (p=0.608) were similar between groups. Only preoperative intraocular pressure was higher in group PC (p=0.005). The mean prediction errors using Haigis, SRK/T, Hoffer Q, Holladay 1, Barrett Universal II, Kane and Hill RBF formulas were all positive in group PC (hyperopic) and all negative (myopic) in group AC. In group PC, there was no significant difference in prediction error between these formulas (p> 0.05). In group AC, the formula with the worst prediction error was Haigis (p=0.001), and the best was Barrett Universal II (p=0.043).Conclusion: The biometric predictability and expected final refraction in phacoemulsification surgery combined with AGV implantation are modified by the position of the tube.Keywords: glaucoma, Ahmed valve, cataract, phacoemulsification, biometry